Karakteristik Saksi Ahli Psikologi Yang Memiliki Kredibilitas - Prasyudhastyka, Chelcian T. K.; Yusti Probowati (Universitas Darul Ulum, 2025)
An expert witness who assists the court needs to have a credible character, so that the testimony or information given is not biased but prioritizes the true facts. Forensic psychology expert witnesses have an important role in various legal processes, both criminal and civil. This article aims to determine the characteristics of forensic psychology expert witnesses who have credibility. This is because the testimony given by forensic expert witnesses can influence the ongoing law enforcement process. This article will use the method literature review. The total number of articles analyzed was 12 articles. The time span of the articles and journals used as references by the author is between 2014 and 2024. The results of literature review The research conducted by the researchers revealed several characteristics of expert witnesses that were considered important, namely academic qualifications, understanding of the applicable legal system, ethics, experience and soft skills. It is very necessary to establish training standards for expert witnesses in the field of forensic psychology through HIMPSI and ASIFOR, so that certification as a Forensic Psychologist or assistant forensic psychologist becomes an important requirement in handling forensic cases.